Quantitative measurement of cerebral oxygen extraction fraction using MRI in patients with MELAS. - Lei Yu (PLoS ONE, 2013)
OBJECTIVE: To quantify the cerebral OEF at different phases of stroke-like episodes in patients with mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) by using MRI. METHODS: We recruited 32 patients with MELAS confirmed by gene analysis. Conventional MRI scanning, as well as functional MRI including arterial spin labeling and oxygen extraction fraction imaging, was undertaken to obtain the pathological and metabolic information of the brains at different stages of stroke-like episodes in patients. A total of 16 MRI examinations at the acute and subacute phase and 19 examinations at the interictal phase were performed. In addition, 24 healthy volunteers were recruited for control subjects. Six regions of interest were placed in the anterior, middle, and posterior parts of the bilateral hemispheres to measure the OEF of the brain or the lesions. RESULTS: OEF was reduced significantly in brains of patients at both the acute and subacute phase (0.266 ± 0.026) and at the interictal phase (0.295 ± 0.009), compared with normal controls (0.316 ± 0.025). In the brains at the acute and subacute phase of the episode, 13 ROIs were prescribed on the stroke-like lesions, which showed decreased OEF compared with the contralateral spared brain regions. Increased blood flow was revealed in the stroke-like lesions at the acute and subacute phase, which was confined to the lesions. CONCLUSION: MRI can quantitatively show changes in OEF at different phases of stroke-like episodes. The utilization of oxygen in the brain seems to be reduced more severely after the onset of episodes in MELAS, especially for those brain tissues involved in the episodes.